Stocking density, restricted trough space, and implications for sheep behaviour and biological functioning - Mayes, Bonnie T.; Tait, L. Amy; Cowley, Frances C.; Morton, John M.; Doyle, Brendan P.; Arslan, Muhammad A.; Taylor, Peta S. (Frontiers in Veterinary Science, 2022)
Stocking density and trough space allowance can potentially impact sheep welfare during live export voyages. The aim of this study was to assess the welfare implications for sheep housed at 5 allometric stocking densities, with either unrestricted or restricted trough space allowance. Merino wethers (n = 720) were housed in 40 pens of 18 head, for 18 days. Two 5-minute continuous focal animal observations (n = 3 / pen) were conducted on days 3, 5, 11 and 17. Scan sampling of standing and lying behaviours were conducted on the same days, at hourly intervals. Liveweights and immune cell counts were quantified at the start and end of the experiment, as well as faecal glucocorticoid metabolites (FGCM), which were also assessed on days 6 and 12. Focal animals housed at higher stocking densities spent less time lying during one of the continuous observation periods, but no important effects on the overall number of animals lying or on the synchronicity of lying were evident. Scan sampling results indicated the expression of some preferred lying positions was impaired at high stocking densities, and high stocking densities also resulted in increased agonistic social interactions and displacement events at the start of the trial. There was a slight reduction in day 18 liveweights for animals housed at higher stocking densities, but FGCM concentrations and immune cell counts were essentially unaffected. Trough space had no important effects on day 18 liveweight, FGCM concentrations or immune cell counts, and limited effects on sheep behaviour. The lack of important impacts on biological fitness traits suggests the behavioural responses observed were sufficient in allowing sheep to cope with their environment. However, we provide evidence that the provision of additional space is beneficial in reducing the time it takes animals to adapt to a novel environment and to facilitate the expression of some preferred lying positions. While designed to emulate certain conditions relevant during live export voyages, some factors that may induce stress during this mode of transport were not present—such as heat and ocean swell—and so the conclusions must be interpreted in the context of the experimental conditions.